2008
DOI: 10.3748/wjg.14.4697
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing bile duct and Stevens-Johnson syndrome associated with ciprofloxacin treated with tacrolimus

Abstract: Stevens-Johnson syndrome (SJS) is a serious and potentially life-threatening disease. Vanishing bile duct syndrome (VBDS) is a rare cause of progressive cholestasis. Both syndromes are mostly related with drugs. We report a case of a patient with ciprofloxacin-induced SJS and acute onset of VBDS, and reviewed the related literature. It is the first case of ciprofloxacin-induced VBDS successfully treated with tacrolimus. This case reminds physicians of the importance of drug reactions, their severity, technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Tacrolimus has had mixed results. 1,3,4 We concluded that the risk/ benefit ratio for tacrolimus in our patient was too high, given his kidney and lung injury. Intravenous immunoglobulin has also been used in adults that developed VBDS secondary to graftversus-host disease and for a patient with VBDS secondary to TEN but was unable to prevent progression to liver transplant in those cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tacrolimus has had mixed results. 1,3,4 We concluded that the risk/ benefit ratio for tacrolimus in our patient was too high, given his kidney and lung injury. Intravenous immunoglobulin has also been used in adults that developed VBDS secondary to graftversus-host disease and for a patient with VBDS secondary to TEN but was unable to prevent progression to liver transplant in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…Refractory cases have used immunosuppression, most commonly the calcineurin inhibitor tacrolimus, with mixed results. 1,3,4 With increased knowledge of the pathophysiology, it has been suggested that tumor necrosis factor-a (TNF-a) inhibitors may represent an alternative therapy. 4 Our patient, a 6-year-old boy, represents the first reported use of a TNF-a inhibitor and plasmapheresis for treatment of VBDS associated with TEN.…”
mentioning
confidence: 99%
See 3 more Smart Citations